The Centrality of Urban Economies to the Study of Competitiveness - Kresl, Peter (2013)
Urban competitiveness has become a primary focal point for the study of public policy during the past quarter century. As cities have become more exposed to challenges posed to their economic activity by other cities, hundreds or thousands of miles distant as well as the opportunities that are offered to them, it has become incumbent on city leaders, in public and private sector functions, to become more active and innovative. This paper examines this new and rapidly evolving global context, how it has influenced city competitiveness and what city leaders can do to ensure the economic future of their residents. It reviews both the meaning and the measurement of urban competitiveness structures in which city economies function and several major issues that arise from urban competitiveness.